Unethical Advertising Practices in the Financial Market and Counteraction Tools - Mazur, Zofia M. (Journal of Finance and Financial Law, 2022)
The purpose of the article/hypothesis. Paper highlights certain crucial aspects of misleading and deceitful advertisings of banking and financial products and services, its effects, and the necessity to ban and/or restrict some of professionals’ misbehaviours. Many research evidence shown how an endless amount of information and specific advertisements can influence consumers’ financial decision-making. This concern was intensified by the impact of COVID-19 on the financial situation of many households. Methodology. Author has conducted extensive research using national and international literature, public reports, legal cases, administrative proceedings, national and international legislations. There are presented some national examples, good principles and suggestions of what should be done to better protect the customers on the banking and financial market. Results of the research. The study revealed that the misleading, abusive conducts and numerous sales strategies of professionals operating on the markets at issue may regard almost any individual. Unethical advertising practices may intensify because of ever-increasing technology and new advertising techniques. As described, both the type and the timing of the advertising can also greatly influence consumers’ choice. The policy makers shall be determined, decisive and fast in order to assure that financial products and services are safe and law-compliant, to raise standards in advertising sector, to prevent defaults, irresponsible borrowing, loss of privacy, discrimination, failures and predatory practices. The measures shall prevent the frauds and the marketing and sales strategies of a set of unrealizable promises or products unsuited to the needs of customers on the financial advertising market.